Daily weight gain of goats until weaning receiving two schemes of mineral supplementation - Pimentel, Viviane Antunes; Malafaia, Pedro Antônio Muniz; Magiero, Karen Purper Freitas; Farias, Mariana de Souza; Deminicis, Bruno Borges; Deminicis, Renata Gomes da Silveira (Revista de Ciências Agroveterinárias, 2023)
The objective of this study was to evaluate the effects of commercial mineral supplementation and selective mineral supplements in which only elements known to be deficient in the animal's diet. In an experiment conducted in Federal Rural University of Rio de Janeiro, Brazil, were analyzed: daily weight gain, nutritional and economic aspects of goats mixed breed receiving two types of mineral supplements. The sixteen animals were divided into two groups. For one group a commercial mineral mixture was used, and to the other group selective mineral mixture containing only sodium (Na) and copper (Cu) was offered. There was no difference in daily weight gain when the selective or commercial mixture was given. The selective mineral supplementation was 4,8 times more economic than conventional supplementation with a commercial mineral mix. The animals showed an increase of hair pigmentation around the eyes, attributed to the correction of copper deficiency. Thus, when an adequate concentrate and good quality forage is given, only the deficient mineral element(s) should be supplemented. The result of this experiment confirms the hypothesis that selective mineral supplementation is correct and can result in reduction of the cost with mineral supplementation of a herd.